Respuestas

2012-07-10T03:43:13+02:00

Hola SoLErA,

 

Raiz cuadrada = sqrt()

 

H = altura = sqrt(13) cm

A = área = 91 cm²

B = Base

D = Diagonal

 

 

Entonces de la fórmula del área despejamos la base.

 

A = B.H
B = A / H 

B = 91 cm² / sqrt(16) cm

B = 25,238858 cm aproximadamente

 

Ahora por pitágoras D es la hipotenusa osea que:

D² =  B² + H²

D = sqrt(B² + H²)
D = sqrt[ (25,238858 cm)² + (sqrt(13) cm)² ]
D = sqrt[ 637 cm² + 13 cm² ] 

D = sqrt[ 650 cm² ]
D = 25,495097 cm aproximadamente